2010
DOI: 10.4103/0970-0218.62579
|View full text |Cite
|
Sign up to set email alerts
|

Isolated systolic hypertension and its determinants - A cross-sectional study in the adult population of Lucknow district in North India

Abstract: Objectives:1) To determine the prevalence of isolated systolic hypertension (ISH) in the adult population of Lucknow district. 2) To study the determinants of ISH especially the relationship with age.Materials and Methods:A community-based cross-sectional study was conducted in four randomly selected areas of Lucknow district. A total of 800 subjects, aged 20 years and above, 400 from urban and 400 from rural area of Lucknow district were included in the study. The statistical tools used for analysis were Pear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
24
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 9 publications
(11 reference statements)
9
24
3
Order By: Relevance
“…[2] Our study also adds the similar evidence. In our study, the prevalence of ISH was found high among current smokers (50%), and the present observation was compared with Gupta et al in Shimla (8.2%), Jagdal et al in Mongolia (10.5%), and Xu et al in China (6.5%), where prevalence of ISH was seen higher among current smokers compared to nonsmokers.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…[2] Our study also adds the similar evidence. In our study, the prevalence of ISH was found high among current smokers (50%), and the present observation was compared with Gupta et al in Shimla (8.2%), Jagdal et al in Mongolia (10.5%), and Xu et al in China (6.5%), where prevalence of ISH was seen higher among current smokers compared to nonsmokers.…”
Section: Discussionsupporting
confidence: 75%
“…In our study, prevalence of ISH was found high among Hindus (26.8%) compared to other religion, whereas a study done by Midha et al in Lucknow reported higher prevalence in others (6.9% Muslim, Christian, and Sikh). [2] The present study revealed the significant association between education and ISH (P < 0.001). Prevalence of ISH was observed high among study subjects who had educated up to primary school (18.1%).…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations